Between uncertainty and individualism. Scientific ethos of adversity and nanotechnology in Peru - Zárate Vásquez, Julio Sebastián (2015)
Practising science in Peru means facing adversity. Due to the country’s recent economic growth and despite its weak institutions, there is a growing (yet insufficient) interest in raising the investment in science, technology and innovation activities. However, how are scientists and engineers overcoming these difficulties? To answer these questions, this research focuses in the study of the experts engaged in scientific practice through the analysis of a particular case: the nanotechnology experts. The main hypothesis of this research is that to overcome these adversities, the nanotechnology experts have developed a peculiar scientific ethos, expressed by an individualized access to knowledge, networks and resources. Taking that into account, the main goal will be to characterize the current institutional situation of science and technology in Peru regarding scientific research.